Trauma-informed youth justice in Canada: a new framework toward a kinder future - Oudshoorn, Judah (Canadian Scholars' Press, 2015)
"This text offers a comprehensive overview of youth justice in Canada and makes the compelling argument that to be effective, youth justice must be trauma-informed. Most youth who come into conflict with the law have experienced some form of trauma, yet most justice professionals are ill-equipped to deal with the effects of trauma on youth, and many justice interventions are ineffective or counterproductive. This text argues that a better framework is needed to understand the context of youth offending, and that this framework will allow for interventions based upon principles of healing rather than punishment."--